(3JMQjQ cJGH GdeLSWis - (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3CMeO Gddg eHOC cd eHOC hZGjI cd ZGjI hHYO abO cfJ HQgI ef GdReGf YGRekG Ydi Cf CMQQ faSi hdSGFQ WdHI GdYde ef GdCNhGf cJGH GdeLSWi s
(3BNQgG (B:s
(3hai NGJeI GdcJGH bGd aEPG JeefG LejY eG jYJUQ Edi EQTGOg ef hLhO eG jMJGL Edi hLhOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3Je Pdc GdMQjQ Ydi jO UGMHg YHO GdcGaF Hf YHO GdeLjO Hf YHO Gddg GdJHQjRi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdadcs